Implikasi Dakwah Musabaqah Tilawatil Qur’an dalam Pembangunan Masyarakat Qur’ani - Abon Ronaldi; Arief Subhan; Arif Zamhari (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2023)
Musabaqah Tilawatil Qur'an (MTQ), which competes for the holy book of Muslims, has received a negative response from some Indonesian Ulama. Because the Qur’an is the authoritative guideline for Muslims whose originality must be maintained. This study aims to be the antithesis of the assumption that MTQ activities are synonymous with disoriented aspects of da'wah. This research is a qualitative field research using an Islamic communication approach. As for access to data from this research, it was obtained by conducting observations, interviews and documentation studies. The research object raised was MTQ activities carried out in Jambi Province. The results of the study concluded that MTQ's preaching had implications for understanding, perception, and changes in people's behavior as an acceleration of the development of the Qur'anic community (Takwin al-Ummah). This research is expected to enrich the body of knowledge in the discipline of da'wah. This means that the da'wah dimension is not only limited to tabligh activities at religious pulpits, but is connected in all social activities of the community.